Managerial analysis of instruments for raising international financing - A. A. Tarasov (Управление)
Syndicated loans and eurobonds are the major mechanisms for raising international financing. In this article the following types of financial instruments available to Russian corporate borrowers in the syndicated loans and eurobonds markets are considered: bridge loans, revolving credit facilities, terms and pre-export loans, project finance; bonds with one/several tranches, ruble-denominated eurobonds, benchmark and long-term bonds.Syndicated loans and eurobonds are complex financial instruments available for corporations with the following profiles: (1) leading 1st and 2nd tier and companies with a track-record of raising international financing; (2) industry leaders (top-5 by market share) with annual revenue exceeding USD 500 mln; (3) companies with a significant share of export operations and foreign currency revenue that is required for the payment of interest and principal amounts of the loans and bonds; (4) borrowers and issuers with credit ratings from the international rating agencies; (5) companies with audited accounts prepared in accordance with IFRS. The SWOT-analysis of these financial instruments is given, as well as the comparative analysis that includes the following parameters: industry specifics, liquidity, publicity.As part of the comparative analysis the execution schedule for syndicated loans and eurobonds transactions is considered. This schedule includes five stages: preparing the corporation for the transaction, working with banks, the syndication process, drafting the legal documentation, receiving the funds by the firm. The main characteristics of syndicated loans include flexibility of the structure, fast execution process and information confidentiality. This is why a syndicated loan is suitable for quickly raising financing from several key banks of the borrower in the case of an acquisition of another company. As the long-term solution, such loans can be then refinanced by eurobonds. The paper concludes that for the leading corporations the optimal choice between loans and bonds lies in the combined use of these instruments to solve various financial problems.